Current and emerging therapies for the treatment of myasthenia gravis - Renato Mantegazza (Dove Medical Press, 2011)
Renato Mantegazza, Silvia Bonanno, Giorgia Camera, Carlo AntozziDepartment of Neuromuscular Diseases and Neuroimmunology, Fondazione Istituto Neurologico Carlo Besta, Milan, ItalyAbstract: Myasthenia gravis (MG) is an autoimmmune disease in which autoantibodies to different antigens of the neuromuscular junction cause the typical weakness and fatigability. Treatment includes anticholinesterase drugs, immunosuppression, immunomodulation, and thymectomy. The autoimmune response is maintained under control by corticosteroids frequently associated with immunosuppressive drugs, with improvement in the majority of patients. In case of acute exacerbations with bulbar symptoms or repeated relapses, modulation of autoantibody activity by plasmapheresis or intravenous immunoglobulins provides rapid improvement. Recently, techniques removing only circulating immunoglobulins have been developed for the chronic management of treatment-resistant patients. The rationale for thymectomy relies on the central role of the thymus. Despite the lack of controlled studies, thymectomy is recommended as an option to improve the clinical outcome or promote complete remission. New videothoracoscopic techniques have been developed to offer the maximal surgical approach with the minimal invasiveness and hence patient tolerability. The use of biological drugs such as anti-CD20 antibodies is still limited but promising. Studies performed in the animal model of MG demonstrated that several more selective or antigen-specific approaches, ranging from mucosal tolerization to inhibition of complement activity or cellular therapy, might be feasible. Investigation of the transfer of these therapeutic approaches to the human disease will be the challenge for the future.Keywords: myasthenia gravis, therapy, immunosuppression, thymectomy, plasmapheresis